Electrochemical Sensing Studies of AsO4−3 Selective Poly(methyl methacrylate)–Zinc Oxide Fibrous Anion Exchanger. Issue 2 (25th May 2016) - Khan, A. A.; Jamil, B.; shaheen, S.
Abstract: Polymethylmethacrylate–ZnO (PMMA–ZnO) fibrous anion exchanger was prepared by solid‐gel method. The structure and morphology of the prepared fibrous anion exchanger were characterized by Fourier transform spectroscopy (FTIR), Field emission Scanning electron microscopy (FE‐SEM), Transmission electron microscopy (TEM), X‐ray diffraction (XRD), thermogravimetric analysis (TGA), and Energy‐dispersive X‐ray (EDX) analysis. The dielectrical constants ( ε ′, ε ″), dielectric loss (tan δ ), and AC conductivity ( σ ac ) were studied as a function of frequency. The material was found to be highly desirable for electroanalytical application as anionic sensor; its membrane electrode has been developed for the detection of AsO 4 − 3 in solutions. The detection limit of AsO 4 − 3 selective membrane electrode is 1 × 10 −9 M to 1 × 10 −1 M with a response time of 35 s and its working pH range is 4–7. The selectivity coefficient values for interfering ions indicate good selectivity for arsenate ( AsO 4 − 3 ) over interfering anions. The accuracy of the results was compared by Portable Coulometric Analyzer (PCA‐Arsenomat).